Green synthesis of silver nanoparticles from cymbopogon citratus and their efficacy against grey blight disease of tea - Mendez, Francis Lijo; Paneerselvam, Nepolean; Joseph, Bewyn; Selladurai, Rishikaran (Journal of Plantation Crops, 2025)
Tea cultivation in India faces significant challenges from biotic and abiotic stresses, necessitating advanced research for sustainable production. Due to acute labour shortages, shearing is commonly practiced in southern tea plantations, often leading to severe grey blight and die-back of shoots caused by Pestalotiopsis theae. This study examines the bioefficacy of silver nanoparticles (AgNPs) green-synthesized from Cymbopogon citratus against grey blight disease in tea. The green synthesis was achieved by treating aqueous extracts of C. citratus with silver nitrate, confirmed through visual and spectrophotometric analysis. The scanning electron microscopy and X-ray diffraction characterization revealed that the nanoparticles were spherical in shape with an average size of 19 nm. The GC-MS chromatographic spectra of C. citratus extract highlighted the presence of hydrazine, 1-(5-hexenyl)-1-methyl-, citral, and geraniol as notable compounds. The in vitro bioefficacy proved that the synthesized AgNPs at 2.0 mL/L manifested complete inhibition of the grey blight pathogen under the Poisoned food technique. Further field evaluation revealed a significant reduction in disease incidence of 62% in the plots treated with AgNPs at 500 mL/ha, which was on par with the standard schedule of Copper oxychloride at 420 g/ha(68%). Therefore, it is concluded that the application of C. citratus-mediated silver nanoparticles is an effective alternative offering a greener strategy, replacing chemical fungicides.